Design and Implementation Iris Recognition System Using Texture Analysis - Ibrahim, Ali A.; J.ODA, Hussein (Nahrain University College of Engineering Journal, 2017)
The aim of this work is to produces a technology of recognition and identifies of the person by using the iris. The work was started by reading the images of eyes (UBIRIS database). After that, the iris region localized from the eye image by using the method of image processing. The iris shape is circular so it transfer to rectangular shape and enhance the image and remove the noise like eyelashes and flash of the camera. Then the image quantized from 256 grey levels to 16 grey levels. Four statistical functions used because these functions give us accurate description of iris, the samples had been taken in four angles. The information for each sample is save in database. The last stage is to classify the samples by using neural network. The results will prove that the work have high accurate conclusions.